MEMBANGUN HUKUM ISLAM YANG BERKEADILAN - Toha Ma’arif (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2014)
Indonesia is a country that is Mayority Islam, but still frequently encountered procedure for most people living in Indonesian Islam is not fully using the guidance that has been taught in the Al-Qur’an and Hadist, it is a consequence of a background that can not be avoided anymore because Indonesian law inherited only from countries that had been occupied it. Considering it is certainly what the Indonesian people did not refers 100% to the laws of Islam, but in tradition law that has prevailed for so long. Writing this article aims to build a just Islamic law in accordance with the teachings of Islam with reference to syadzali munawir thinking and knowing the prospect of Islamic law as applied in Indonesia. From the results of the analysis can be in the know that the prospect of the application of Islamic law in Indonesia is ideal because in practice the application of Islamic law would have much streght and solutions that are ready to overcome any weaknesses.